2018
DOI: 10.5194/hess-22-709-2018
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven disturbances in the San Juan River sub-basin of the Colorado River

Abstract: Abstract. Accelerated climate change and associated forest disturbances in the southwestern USA are anticipated to have substantial impacts on regional water resources. Few studies have quantified the impact of both climate change and land cover disturbances on water balances on the basin scale, and none on the regional scale. In this work, we evaluate the impacts of forest disturbances and climate change on a headwater basin to the Colorado River, the San Juan River watershed, using a robustly calibrated (Nas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 87 publications
0
40
0
Order By: Relevance
“…Moreover site-level observations (Alfaro-Sánchez et al 2015; Dore et al 2012;Nolan et al 2014a) and process-based hydroecological models (Komatsu and Kume 2020) can better interpret the biophysical mechanisms by partitioning ET, and by analyzing the effects of vegetation loss and recovery (Goeking and Tarboton 2020; Kinoshita and Hogue 2015; Komatsu and Kume 2020). Some previous studies have concluded that canopy loss has a marginal impact on ET, either due to increased subcanopy radiation and evaporation, and/or rapid post disturbance recovery (Bennett et al 2018;Biederman et al 2015;Goeking and Tarboton 2020). Cross-comparing results between data-driven and physically based modeling studies may prove useful for reconciling these results, while bringing deeper insights into how and why ET is affected by wildfire (Bart et al 2016;Federer and Lash 1978).…”
Section: Limitations and Future Research Needsmentioning
confidence: 97%
“…Moreover site-level observations (Alfaro-Sánchez et al 2015; Dore et al 2012;Nolan et al 2014a) and process-based hydroecological models (Komatsu and Kume 2020) can better interpret the biophysical mechanisms by partitioning ET, and by analyzing the effects of vegetation loss and recovery (Goeking and Tarboton 2020; Kinoshita and Hogue 2015; Komatsu and Kume 2020). Some previous studies have concluded that canopy loss has a marginal impact on ET, either due to increased subcanopy radiation and evaporation, and/or rapid post disturbance recovery (Bennett et al 2018;Biederman et al 2015;Goeking and Tarboton 2020). Cross-comparing results between data-driven and physically based modeling studies may prove useful for reconciling these results, while bringing deeper insights into how and why ET is affected by wildfire (Bart et al 2016;Federer and Lash 1978).…”
Section: Limitations and Future Research Needsmentioning
confidence: 97%
“…Changing land cover often alters the relation for finite periods, for example, the time needed for a forest to recover and regrow from insect infestation‐induced tree mortality or wildfire. The relation may also be altered if regrowth results in structurally different land cover (Bennett et al 2018), especially important given predicted temperature‐driven forest disturbance (McDowell et al 2016; McDowell et al 2018). Several other factors also can alter the SWE‐streamflow relation, including periods of drought, shifts or changes in seasonal patterns (e.g., timing of precipitation events), and changes in climatic influences on snowpack (e.g., temperature).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the impacts of climate and landscape change in the SJR basin, we used the Variable Infiltration Capacity (VIC) hydrologic model (version 4.2) to simulate natural streamflow for the CRB [14]. VIC was newly calibrated for the entire CRB to develop revised parameters for soils, vegetation, elevation bands to better capture flow within the sub-watersheds of the basin, under recently released historical climate data.…”
Section: Models and Datamentioning
confidence: 99%
“…For instance, streamflow in the CRB headwaters is projected to decrease by up to 40% by some Earth System Models [13]. Changes such as these have cascading impacts resulting in ecosystem disturbances [14], impaired water quality [15], reduced agricultural productivity, vegetation mortality [16], wildfires [17,18], and infestations of insects and pathogens [19,20].…”
Section: Introductionmentioning
confidence: 99%